Desarrollo de la afectividad infantil. - Paladines Chango, Karla Ingrid (2015)
The present research seeks to identify the process of child emotional development approach relying of the Historical, Cultural, analyzed qualitatively on the factors that contribute to the child emotional development, family first, by being the first social environment of interaction between the individual, second school, considered as the second home of the people in where mutually values learned from the family and as a last factor, the socio-cultural, in this way the subject will proceed to take action in your environment by bringing new interpersonal relationships that will be significant for her emotional state, another point that highlights the approach mentioned above is the importance of this affective development partner for the personal growth of the child, with emphasis on the child rearing practices that use the Parents in the education of their children, that is to say, the rules, limits or punishments that use, it also highlights the affective relationships, social skills, emotional ties, solution of conflicts that drive the subject under study, in this case, there will be an analysis of case in the canton Camilo Ponce Enriquez to a less than 8 years that reflects autonomy in their activities through the education of their parents and a teacher at the school who have utilized the use of standards, values, rules, demonstrations of affection to guide the emotional development of the child thus creating warm affective relationships that also contribute to this process. The methodology of the present text is qualitative, this model allows you to analyze the characteristics of the subject under study through a biographical analysis to know with greater validity their skills or flaws that have developed in various stages of their lives. For the acquisition of information has been used techniques such as: the psychological interview and observation, through both information has been obtained the patient's real assisting in the drafting of the history of the same personologica, assessing RAIS in every area of social interaction: area family, school, affective loving, personal and social.